Reduced Plasma Levels of α-Klotho and Their Correlation With Klotho Polymorphisms in Elderly Patients With Major Depressive Disorders - Gao, Xiang; Sun, Zuoli; Ma, Guangwei; Li, Yuhong; Liu, Min; Zhang, Guofu; Xu, Hong; Gao, Yane; Zhou, Jixuan; Deng, Qi; Li, Rena (Frontiers in Psychiatry, 2021)
Background: Recent literature suggests that α-Klotho, a widely recognized anti-aging protein, is involved in longevity as well as in many diseases, including Alzheimer’s disease and depression. Although the Klotho gene encodes α-Klotho, a single transmembrane protein with intracellular and extracellular domains, the relationship between Klotho gene polymorphism and circulating α-Klotho levels in patients with major depressive disorder (MDD) is not clear. Methods: A total of 144 MDD patients and 112 age-matched healthy controls were included in this study. The Klotho genetic polymorphisms (rs9536314, rs9527025 and rs9315202) and plasma α-Klotho levels were measured by PCR and ELISA, respectively. The severity of depressive symptoms was estimated using the Hamilton Depression Scale (HAMD). Results: We found a significantly lower level of plasma α-Klotho in the MDD patients than in controls. Among them, only elderly MDD patients (first episode) showed significantly lower α-Klotho levels than the age-matched controls, while elderly recurrent and young MDD patients showed no difference in plasma α-Klotho levels from age-matched controls. The young MDD group showed a significantly earlier onset age, higher plasma α-Klotho levels, and lower HAMD scores than those in the elderly MDD group. While the plasma α-Klotho levels were higher in rs9315202 T alleles carrier regardless age or sex, the rs9315202 T allele was negatively correlated with disease severity only in the elderly MDD patients. Conclusion: The results of our study showed that only elderly MDD patients showed a decrease in plasma α-Klotho levels along with an increase in disease severity as well as an association with the number of rs9315202 T alleles, and not young MDD patients compared to age-matched controls. Our data suggest that circulating α-Klotho levels combined with Klotho genetic polymorphisms are important in elderly MDD patients, particularly carriers of the Klotho gene rs9315202 T allele.